Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10826-010-9443-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Individualized Parent Advocate Services in Children’s Mental Health: A Contextualized Theoretical Application

Abstract: Scant research literature exists documenting the details of services rendered by peer support providers and their relative impact on children and families. The specific services delivered by peer providers, how the provision of such services are determined and tailored to the needs of individual families, and the tools used to gather services information are largely unknown. We examined how ''parent advocates'' in the state of Ohio conducted their work with families served through publicly funded children's me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
1
14
0
3
Order By: Relevance
“…Wisdom et al (2011) found that the walkthrough process was both feasible and acceptable to FSS as a way of evaluating services. Consistent with previous studies (Davis et al, 2011; Rodriguez et al, 2011), there was substantial variability in services provided by FSSs.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Wisdom et al (2011) found that the walkthrough process was both feasible and acceptable to FSS as a way of evaluating services. Consistent with previous studies (Davis et al, 2011; Rodriguez et al, 2011), there was substantial variability in services provided by FSSs.…”
Section: Introductionsupporting
confidence: 89%
“…In Rodriguez et al (2011), FSSs described their job functions, demonstrating that FSS provided a variety of services, including information/education, one-on-one advocacy, tangible assistance (e.g., childcare, transportation vouchers) parenting skills, and emotional support. Davis, Gavazzi, Scheer, & Uppal (2011) conducted qualitative interviews with parent advocates to understand specific activities when working with families in publicly funded mental health programs. They described their day-to-day activities as including service system advocacy and support, parent education and empowerment, emotional and social support, resource information and linkage, and material services and supports (e.g., transportation).…”
Section: Introductionmentioning
confidence: 99%
“…Participants described health and education special needs services as complex and confusing, a sentiment documented in prior literature (e.g., [45]). Echoing Davis et al [13], participants reported that they relied heavily on veteran parents on social media sites to learn about IEPs and to prepare for their IEP meeting.…”
Section: Needs-based Search: Finding Other Parentsmentioning
confidence: 99%
“…from interviews with Pst providers we learned that one common action taken in practice to help caregivers feel hopeful is organization of groups of other caregivers to provide opportunity for group learning and social support. This activity is one example of an intervention that alone has the potential to meet all goals of the underlying theory of this intervention (ireys et al, 2002): it provides opportunities for caregivers to establish community ties that may lead to an increased sense of social support and empowerment; opportunities for community-building, networking, and advocacy; and an outlet for reciprocity and social comparison (davis, Gavazzi, scheer, & uppal, 2011). This component also had a highfrequency rating (4.46), indicating that it is frequently being carried out, thus showing evidence through this example that the goals of the underlying theory are generally being upheld in practice in Kansas.…”
Section: Discussionmentioning
confidence: 99%
“…findings from this study provide a template for program development that is theory based and family driven. use of concept mapping allowed us to identify components of a model that had support in the literature as well as with stakeholders, thus contributing to the development of a sound model that will likely demonstrate efficacy in translation to community settings (davis et al, 2011;Munson et al, 2009;rodriguez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%